Assessment of level of anxiety among the patients of knee osteoarthritis visiting the different Hospitals across Sindh and Balochistan - Aadil Ameer Ali; Natasha Bhutto; Shobha Lekhraj; Sonum Sachdev; Noman Haq; Arsum Shaikh & Shabana Yasmin (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2021)
Objective: To evaluate the level of Anxiety among the Patients of Knee Osteoarthritis.  Methodology: A cross sectional survey was conducted in different hospitals of Sindh and Balochistan province, Pakistan from June to October 2020. A self-fabricated questionnaire was used in in already diagnosed 292 patients of Knee Osteoarthritis (KOA) which consist of the demographic and disease related questions. The statistical package for social sciences (SPSS) version 23 was used to interpret the data. Result: The majority (n=160, 54.8%) were male and (n=234, 80.1%) having age between 61 to 63 years. Mostly (n=115, 39.4%) were found graduate in educational status and (n=25, 73.6%) were the permanent resident of urban area. After checking the level of anxiety we found that majority (n=118, 40.4%) were mild anxious due to disease (KOA). Conclusion: The study finalized that the patients who are suffering from Knee Osteoarthritis (KOA) were found mild anxious because the KOA patient faces the somewhat disability in later stages which puts a socioeconomic burden on patients life that leads to anxiety and depression.